Effect of rice lines transformed with Bacillus thuringiensis toxin genes on the brown planthopper and its predator Cyrtorhinus lividipennis - Bernal, Carmencita C.; Aguda, Remedios M.; Cohen, Michael B. (Wiley, 2002)
Five transgenic rice lines, each containing an insecticidal toxin gene from Bacillus thuringiensis (Bt) under control of a different promoter, were tested for effects on two non‐target insects: the brown planthopper, Nilaparvata lugens (Stål) (Homoptera: Delphacidae), and its predator Cyrtorhinus lividipennis (Hemiptera: Miridae). Bt toxin was detected by ELISA in the honeydew of N. lugens that fed on rice lines with the CaMV 35S and actin promoters. Nilaparvata lugens produced greater volumes of acidic honeydew (derived from xylem feeding) on all five Bt rice lines than on non‐transgenic control lines. The amount of honeydew derived from phloem feeding did not differ between Bt and control lines. There were no differences between N. lugens reared on Bt and control lines in any of the five fitness parameters measured (survival to the adult stage, male and female weight, and male and female developmental time). There were no differences between C. lividipennis reared on N. lugens nymphs from Bt and control lines, in any of the three fitness parameters examined (survival to the adult stage and male and female developmental time). Our results indicate that N. lugens and its natural enemies will be exposed to Bt toxins from rice lines transformed with some Bt gene constructs, but that this exposure might not affect N. lugens and C. lividipennis fitness.